Collaborative Reasoning Technique in Developing Moral Comprehension - Wahyuningsih, Lenny; Solehuddin, M.; Dahlan, Tina Hayati (Islamic Guidance and Counseling Journal, 2019)
This study aims to find out about the collaborative reasoning technique to develop students' Moral Comprehension in class X of State High School 1 Gegesik. The research approach used was the quasi-experimental method and non-equivalent control group research design. Research instruments using the Defining Issue Test (Rest's DIT-1). The results of the research are: (1) the Moral Comprehension of students is generally in stage 4; (2) the results of the dissemination of DIT-1 instruments; and (3) guidance and counseling programs with collaborative reasoning proven effective in developing students' Moral Comprehension with changes in the stages of Moral Comprehension of students. Success criteria due to more than 50% of students are in steps 4, 5 and 6.